2003
DOI: 10.1159/000070991
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C in Chronic Kidney Disease and Hemodialysis Patients

Abstract: Increments of oxidative stress have been addressed as one potential cause for the accelerated atherosclerosis of chronic kidney disease patients. Ascorbate represents one of the most prominent antioxidants both in plasma as well as intracellulary, exerting beneficial effects by an inhibition of lipid peroxidation and by reducing endothelial dysfunction. However, in the presence of transition metals like iron, ascorbate may give rise to an increased generation of oxidants, and ascorbylation may impose additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 62 publications
3
61
0
1
Order By: Relevance
“…Plasma vitamin C levels of chronic renal failure and dialysis patients are lower when compared with healthy subjects (17,19), and associations with elevated amounts of various (per) oxidation products or deficiencies in antioxidants have been reported frequently (31)(32)(33). Evidence, however, for a causal link between a low vitamin C status and increments of oxidative stress parameters is limited.…”
Section: Generalizability Of Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma vitamin C levels of chronic renal failure and dialysis patients are lower when compared with healthy subjects (17,19), and associations with elevated amounts of various (per) oxidation products or deficiencies in antioxidants have been reported frequently (31)(32)(33). Evidence, however, for a causal link between a low vitamin C status and increments of oxidative stress parameters is limited.…”
Section: Generalizability Of Findingsmentioning
confidence: 99%
“…Vitamin C represents the primary antioxidant defense in blood (18), and nonsupplemented maintenance hemodialysis patients are at high risk for vitamin C deficiency (19). A significant proportion of multivitamin-supplemented patients still exhibits plasma levels that are well below the reference range of healthy, nonsmoking, middleaged European residents (20).…”
mentioning
confidence: 99%
“…Moreover, the activity of the enzymatic and non-enzymatic antioxidant system is diminished. These unfavorable phenomena exaggerate CRF-related complications, such as atherosclerosis and associated cardiovascular complications, accelerated ageing, β 2 -microglobulin arthropathy, defective deformability of erythrocytes, cataract, anemia, increased hemolysis and platelet dysfunction [1,2,3,4,5,6]. Such oxidative stress can also accelerate the apoptosis of leukocytes in hemodialyzed (HD) patients [7].…”
Section: Introductionmentioning
confidence: 99%
“…In case of patients who are not on dialysis, the reduced values are attributed to the urinary losses. 16 VA DeBari et al (1984) also observed that the levels of ascorbate were significantly reduced in the hemodialysis patients. 15,17 Marion Morena et al reported that patients who were subjected to hemodiafiltration session with highly permeable membranes showed a decreased vitamin C level.…”
Section: Discussionmentioning
confidence: 94%